Unlocking the Potential of OLT for Startup ISPs in Indonesia: Challenges and Strategies - Mustofa, Dinar; Saputra, Dhanar Intan Surya; Kusuma, Velizha S; Aminuddin, Afrig; Wirasto, Anggit; Apitiadi, Satyo Dwi (Journal of Information System and Informatics, 2024)
This study explores the implementation of Optical Line Terminal (OLT) technology by Internet Service Providers (ISPs) startups in underserved and remote areas of Indonesia, examining its effectiveness, challenges, and opportunities. The research reveals that OLT technology can significantly improve internet service quality, with measurable increases in speed (up to 30%) and reliability (20% improvement), especially in rural areas. However, ISP startups face several technical challenges, including inadequate fiber optic infrastructure, high initial investment costs, and the complex geographical conditions across Indonesia’s diverse islands. Regulatory barriers, such as lengthy licensing processes and inconsistent policies, further hinder the deployment of OLT technology. Despite these challenges, the study identifies key opportunities for ISP startups to overcome these obstacles. Collaboration with government initiatives like the Palapa Ring and the potential integration with 5G and IoT technologies can reduce costs and accelerate network deployment. Additionally, leveraging existing infrastructure enables faster expansion of broadband services, particularly in remote regions. The research also finds that ISP startups adopting OLT technology can significantly narrow the digital divide by expanding service coverage in underserved areas, with a noted 25% increase in digital inclusion. These findings offer valuable insights for policymakers and business leaders, informing strategies to optimize OLT technology and foster a more equitable digital transformation across Indonesia, particularly in expanding access to broadband internet in marginalized regions.